2020
DOI: 10.1016/j.ebiom.2020.103054
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence quantified tumour-stroma ratio is an independent predictor for overall survival in resectable colorectal cancer

Abstract: Background An artificial intelligence method could accelerate the clinical implementation of tumour-stroma ratio (TSR), which has prognostic relevance in colorectal cancer (CRC). We, therefore, developed a deep learning model for the fully automated TSR quantification on routine haematoxylin and eosin (HE) stained whole-slide images (WSI) and further investigated its prognostic validity for patient stratification. Methods We trained a convolutional neural network (CNN) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
100
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(107 citation statements)
references
References 29 publications
6
100
1
Order By: Relevance
“…In recent years, convolutional neural networks (CNN) and other deep learning algorithms have been established as state-of-the-art methods for a wide field of image classification tasks. CNNs for the quantification of tumor stroma proportion have already been developed [ 18 ], and it has been shown that tumor budding can be validly determined using machine learning methods [ 19 ]. For a comprehensive review of deep learning in colon cancer, we refer to Pacal et al [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, convolutional neural networks (CNN) and other deep learning algorithms have been established as state-of-the-art methods for a wide field of image classification tasks. CNNs for the quantification of tumor stroma proportion have already been developed [ 18 ], and it has been shown that tumor budding can be validly determined using machine learning methods [ 19 ]. For a comprehensive review of deep learning in colon cancer, we refer to Pacal et al [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this article of EBioMedicine , Ke Zhao and colleagues [1] show that it is possible to quantify the tumour-stroma percentage by artificial intelligence, using a convolutional neural network on whole-slide images (WSI). Moreover, the prognostic effect of the tumour-stroma ratio (TSR) for overall survival was confirmed, showing the robustness of the TSR method.…”
mentioning
confidence: 99%
“…Research is exploring possibilities of developing new algorithms to support the pathologists in daily practice and to reduce their workload. Most of the algorithms are still only used in research setting, but look quite promising, as is the algorithm developed by Zhao et al [1] .…”
mentioning
confidence: 99%
See 2 more Smart Citations